2011
DOI: 10.4103/1947-489x.210845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antidiarrheal activity of methanol leaf extract of Bombax Buonopozense in rats

Abstract: Objectives: The methanolic extract of the leaves of Bombax buonopozense was screened for antidiarrheal effects. Materials and methods: The extract was evaluated for castor oil-induced diarrhoea and enteropooling as well as intestinal transit in rats. Results: Bombax buonopozense significantly (p<0.05) and dose-dependently reduced frequency of stooling in castor oil-induced diarrhoea, castor oil-induced enteropooling and intestinal motility in rats. The oral LD 50 values obtained were greater than 5000mg/ kg in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 15 publications
(14 reference statements)
3
29
0
Order By: Relevance
“…The methanolic leaf extract of Bombax buonopozense was found to possess antidiarrhoael, antinociceptic, anti-imflammatory, antipyretic and antimalarial activities. [24][25][26] The results obtained in the present study justify the use of the extracts of Bombax buonopozense leaves and roots in traditional medicine for the treatment of microbial disease, especially those caused by S. bioassay-guided fractionation and further characterization of the active constituents responsible for the antimicrobial potential of this medicinally important plant is under way in our laboratory.…”
Section: Discussionmentioning
confidence: 95%
“…The methanolic leaf extract of Bombax buonopozense was found to possess antidiarrhoael, antinociceptic, anti-imflammatory, antipyretic and antimalarial activities. [24][25][26] The results obtained in the present study justify the use of the extracts of Bombax buonopozense leaves and roots in traditional medicine for the treatment of microbial disease, especially those caused by S. bioassay-guided fractionation and further characterization of the active constituents responsible for the antimicrobial potential of this medicinally important plant is under way in our laboratory.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, we have shown the experimental data for one dose (200 mg/kg) only, for both extracts. There are many reports on anti-diarrehal activity of plant extract using this dose level [24] . Loperamide, apart from regulating the gastrointestinal tract, is also reported to slow down transit in the intestine, reduce colon flow rates and consequently have any effect on colonic motility [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, they were observed for 4 hours for the presence of diarrhea defined as watery (wet), unformed stool. (Akuodor et al, 2011).…”
Section: Antidiarrheal Activitymentioning
confidence: 99%